Surviving the Cretaceous-Paleogene mass extinction event: A terrestrial stem turtle in the Cenozoic of Laurasia - Pérez-García, Adán (Sci Rep, 2020)
Findings of terrestrial stem turtles are not uncommon at Mesozoic continental sites in Laurasia, especially during the Upper Cretaceous. Thus, the record of several lineages is known in uppermost Cretaceous ecosystems in North America (Helochelydridae), Europe (Helochelydridae and Kallokibotion) and Asia (Sichuanchelyidae). No terrestrial stem turtle had been described in Laurasia after the Cretaceous-Paleogene mass extinction event. Thus, the only representatives described in the Cenozoic record worldwide corresponded to forms from southern Gondwana, where some of them survived until the Holocene. A bizarre terrestrial stem turtle from the upper Thanetian (upper Paleocene) of Europe is described here: Laurasichersis relicta gen. et sp. nov. Despite its discovery in France, in Mont de Berru (Marne), this Laurasian taxon is not recognized as a member of a European clade that survived the Cretaceous-Paleogene extinction event. It belongs to Sichuanchelyidae, a hitherto exclusively Asian Mesozoic group, known from the Middle Jurassic. Finds at the Belgian site of Hainin (Hainaut) show that this dispersion from Asia and the occupation of some niches previously dominated by European Mesozoic terrestrial stem forms had already taken place a few million years after the mass extinction event, at the end of the lower Paleocene.